Animal rights – a philosophical inquiry - Szopka, Marta (ETHICS IN PROGRESS, 2014)
Review of: Dorota Probucka (2013). Filozoficzne podstawy idei praw zwierząt [Philosophical foundations of the animal rights concept], pp. 352, Cracow: Universitas